2021
DOI: 10.32722/arcee.v2i02.3628
|View full text |Cite
|
Sign up to set email alerts
|

Improving The Performance of Asphalt Concrete Mixtures With Polymer Asphalt in Submerged Floods

Abstract: The road conditions which is always submerged can reduce the performance of the asphalt pavement. This research was conducted to obtain the characteristics of polymer asphalt concrete against flooding. Marshall testing was carried out on conventional and polymer asphalt concrete with optimum asphalt content treated with water immersion in variations of 0 days, 0.5 days, 1 day, 2 days, and 4 days. The results show polymer asphalt can improve the durability of asphalt concrete which is submerged in floodwater. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…(Amri et al, 2023) reported that their FLG could increase the Marshal stability value of asphalt are about 5.1% to 17.6% when 3 to 9% FLG are added at concentrations of 10 to 30 mg/ml. This effect was also observed by (Yanuar et al, 2021). In fact, the stability value of the polymer asphalt mixture has a higher stability value than the stability of conventional asphalt mixture and the difference in the stability value was about 113% higher.…”
Section: Effect Of Melted Wpb Addition On the Marshall Stabilitysupporting
confidence: 56%
See 2 more Smart Citations
“…(Amri et al, 2023) reported that their FLG could increase the Marshal stability value of asphalt are about 5.1% to 17.6% when 3 to 9% FLG are added at concentrations of 10 to 30 mg/ml. This effect was also observed by (Yanuar et al, 2021). In fact, the stability value of the polymer asphalt mixture has a higher stability value than the stability of conventional asphalt mixture and the difference in the stability value was about 113% higher.…”
Section: Effect Of Melted Wpb Addition On the Marshall Stabilitysupporting
confidence: 56%
“…The need for high-quality, and sustainable road infrastructure is partly due to the new load configurations of heavy goods vehicles, and partly to the need to improve the durability of road pavements (Junod & Dumont, 2004). Road damage is attributed to excessive loads, natural disasters, and construction quality, wherein the composition and design of construction material play a big role (Yanuar et al, 2021). Asphalt in its traditional configuration no longer provides satisfactory resistance to rutting under theses constraints (Allah et al, 2015;Cuisinier et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation